KEMAMPUAN BERPIKIR KRITIS MAHASISWA DALAM MENYELESAIKAN SOAL ANALISIS MELALUI PEMBELAJARAN MATEMATIKA BERDASARKAN MASALAH - Santoso, Fransiskus Gatot Iman (Jurnal Edukasi Matematika dan Sains, 2013)
The research was conducted aimed to determine students critical thinking skills in solving problems in the course of analysis Geometric Transformations through problem based learning in mathematics. The ability to think critically examined is the ability to solve problems, in this matter of the analysis, the correct procedure and reasoned, correctly draw conclusions based on the facts and the arguments are valid. Students critical thinking skills in solving problems related to the analysis of subject matter Geometric Transformations, namely translational, half-round, reflection and rotation. This research is descriptive qualitative approach. This study was conducted at Catholic University of Widya Mandala Madiun, and research subjects are students majoring in Mathematics Education Geometric Transformations course overflow Even semester academic year 2011/2012. Data collection techniques in this study using a test method, namely Critical Thinking Test. The results of this study are based on learning mathematics through problem obtained that the average Critical Thinking Skills (CBC) students in solving problems overall analysis on the subject Transformation Geometry of 5.53 and qualifies as being critical thinking skills.Keywords: Critial Thinking Skills, Problem Based Learning Mathematics